Signs from the future, phantoms of the past: On automation and technological transformation in late capitalism - Navarro Ruiz, Clara (2025)
Digital Economy appears to be the future of the capitalist economic system. In these lines we explain some of its main characteristics. In order to do so, we analyze some of the transformations implied by the use of ICTs in the production process and tackle the business model of the GAFA companies following Philipp Staab. We conclude by approaching the automation phenomenon in relation with employment loss thanks to Aaron Benanav’s argumentation.